Frailty in the Elderly Understanding and Managing Complexity - Palermo, Sara (IntechOpen, 2021)
The progressive growth in the number of older adults worldwide has led to a modification of the current healthcare scenario and a parallel increase in the use of public resources. In this book, we propose a conceptual framework within which aging, frailty, and care are analyzed through the lens of complexity medicine. Therefore, we present a multidimensional perspective that takes into account biomedical, (neuro)psychological, and socio-ecological vulnerability. The theses presented are the result of an inductive approach, based on many years of experience in the field, which has made it possible to identify strategies for frailty recognition and effective responses even in complicated clinical settings. The book is intended to be a tool of concrete and easy consultation, rich in reflections and suggestions.